The Effect of the Project-Based Learning Model on Fourth Grade Students` Learning Outcomes in the Pancasila Principles at SDN Tlesa Pamekasan - Wahyu, Dzikri; Dian Sumadi, Conny (Yayasan Citra Dharma Cindekia, 2026)
This study aimed to examine the effect of the Project-Based Learning model on the learning oucomes of fourth-grade students. This research was conducted based on classroom observations indicating that students` learning outcomes were not optimal because teachers tended to use lecture based methods with limited variation in learning models. The study employed a quantitative approach using a non- equivalent control group design. The research sample consisted of fourth grade sudents selected through purposive sampling. Hypothesis testing wa conducted using an independent samples t-test. The result showed a significant difference between the pretest and posttest mean scores of students in the ecperimental class. The t-test analysis revealed a significance value 0f 0.003, which was lower than 0.05, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. Therefore, it can be concluded that the Project Based Learning model has a significant effect on students` learning outcomes.